Analisis Technology Acceptance Model Terhadap Kualitas Informasi Akuntansi pada Organisasi Perangkat Daerah Kabupaten Badung - Ni Wayan Kresnawati; Gede Juliarsa (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The quality of accounting information is a crucial factor in decision making in the public sector, including in Regional Government Organizations (OPD). Quality accounting information must be relevant, accurate, reliable, and timely. However, in its implementation, there are still obstacles in producing accounting information that is not optimal, such as the lack of utilization of information technology, low expertise and intensity of use of accounting information systems, and the level of user satisfaction that is not yet optimal. The purpose of this study is to empirically prove information technology, user expertise, user intensity, ease of use and user satisfaction with the quality of accounting information at the Regional Government Organization Office of Badung Regency. The determination of the number of samples used purposive sampling and obtained a sample of 140 respondents. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that information technology, user expertise, user intensity, ease of use and user satisfaction affect the quality of accounting information. The theoretical implications of this study indicate that the results of this study can support Tam's theory. On the other hand, the practical implications of this study can be used as a consideration for local governments in decision making.